2018
DOI: 10.1128/jcm.01124-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Orientia chuto in Trombiculid Chigger Mites Collected from Wild Rodents in Kenya

Abstract: We present data that concurs with the reported geographical expansion of scrub typhus outside the “Tsutsugamushi Triangle” and addition ofOrientia chutoas a second species in theOrientiagenus. Wild rodents were caught in Marigat, Baringo County, Kenya, and ectoparasites, including chiggers, were recovered. Rodent and chigger species were identified by taxonomic features. DNA was extracted from the chiggers and used to amplify and/or sequence the 47-kDa high temperature transmembrane protein (TSA47), the 56-kDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…Although scrub typhus in Asia-Pacific is transmitted by chiggers, in Chile and other possible newly identified endemic regions, the vector is unknown. Interestingly, a study from 2018 found the first molecular evidence for Candidatus Orientia chuto infection of chiggers collected from a rodent in Kenya [31], another region outside the tsutsugamushi triangle, where scrub typhus might occur as suggested by two recent retrospective surveys, detecting antibodies to Orientia spp. in 3% to 5% of febrile patients [5,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although scrub typhus in Asia-Pacific is transmitted by chiggers, in Chile and other possible newly identified endemic regions, the vector is unknown. Interestingly, a study from 2018 found the first molecular evidence for Candidatus Orientia chuto infection of chiggers collected from a rodent in Kenya [31], another region outside the tsutsugamushi triangle, where scrub typhus might occur as suggested by two recent retrospective surveys, detecting antibodies to Orientia spp. in 3% to 5% of febrile patients [5,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although scrub typhus in Asia-Pacific is transmitted by chigger mites, in Chile and other possible endemic regions, the vector is unknown. Interestingly, a study from 2018 found first molecular evidence for Orientia chuto infection in chiggers collected from a rodent in Kenya [29], another region outside the tsutsugamushi triangle, where scrub typhus might occur as suggested by two recent retrospective surveys, detecting antibodies to Orientia spp. in 3% to 5% of febrile patients [5,29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study from 2018 found first molecular evidence for Orientia chuto infection in chiggers collected from a rodent in Kenya [29], another region outside the tsutsugamushi triangle, where scrub typhus might occur as suggested by two recent retrospective surveys, detecting antibodies to Orientia spp. in 3% to 5% of febrile patients [5,29]. In the endemic regions in Asia-Pacific, the disease is transmitted by different Leptotrombidium species; however, mites of this genus are not endemic in Chile or any other region of the Neotropics [30].…”
Section: Discussionmentioning
confidence: 99%
“…7 Recently, a novel Orientia species, Orientia chuto, has been described from a patient in Dubai and from mites in Kenya, indicating the possibility of becoming an emerging pathogen. 8,9 Other Rickettsioses In addition to the above three groups of diseases, human ehrlichiosis and anaplasmosis, and Q fever caused by Coxiella burnetii are also frequently included under the term rickettsioses.…”
Section: Scrub Typhusmentioning
confidence: 99%